Genealogi Pemikiran Islam Washatiyah KH. Hsyim Asy’ari dalam Hukum Keluarga - Hustina Hustina; Nailal Muna; Anjani Putri Yasnu (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Building family relationships is not just about combining two people of different types. The marriage process can also be interpreted as a merging of functional human values ​​in different societies. Married couples become a part of the social structure which is expected to have roles and functions in society. This perspective is one of KH's concentrations. Hasyim Asy'ari is the founder of Nahdlotul Ulama in Indonesia and a role model for society in the religious life of the nation and state. In order to explore these great ideas, this article thoroughly examines the book Dhou Misbah fi ahkam An Nikah, which is the basis for some people to give marriage advice. This research uses a structuralist functionalist transformation approach within the framework of religious doctrine. This research uses book reference sources which form the basis of thought in the book Dhou Misbah fi ahkam An Nikah and books on religious movements and sociology. As a result, fragments of KH's thoughts. Hasyim Asy'ari regarding the family in its social function is that it must be able to strengthen religious values ​​with local wisdom. Thus, washatiyah Islam is a reflection of values ​​that must be implemented in family life. When starting a family, husband and wife must take a role in building an Islamic society without eliminating local culture. The family must be part of supporting harmony in religious, national and state life.